Allostatic load as a tool for monitoring physiological dysregulations and comorbidities in patients with severe mental illnesses - Bízik, Gustáv; Picard, Martin; Nijjar, Rami; Tourjman, Valérie; McEwen, Bruce S; Lupien, Sonia J; Juster, Robert-Paul (Harvard review of psychiatry, 2013)
Severe mental illnesses like schizophrenia and bipolar disorder are disabling, chronic conditions that are often accompanied by medical comorbidities. In this theoretical article, we review the allostatic load model representing the "wear and tear" that chronic stress exacts on the brain and body. We propose an innovative way of monitoring physical and psychiatric comorbidities by integrating the allostatic load model into clinical practice. By interpreting peripheral biomarkers differently, medical professionals can calculate a simple, count-based, allostatic load index known to predict diverse stress-related pathologies. In addition to screening for comorbidities, allostatic load indices can be used to monitor the effects of pharmacological and psychosocial interventions. This framework can also be used to generate a dialogue between patient and practitioner to promote preventive and proactive approaches to health care.
Keywords: stupeň závažnosti nemoci; Mental Disorders; komorbidita; alostáza; lidé; Severity of Illness Index; Comorbidity; Allostasis; duševní poruchy; Humans